2015
DOI: 10.1002/pola.27672
|View full text |Cite
|
Sign up to set email alerts
|

Bioreducible hyperbranched polyglycerols with disulfide linkages: Synthesis and biocompatibility evaluation

Abstract: In this article, we describe the development of multifunctional, water-soluble hyperbranched polyglycerols containing redox-sensitive disulfide linkages as a new class of biodegradable polymers. The polymers were synthesized by the anionic ring opening multibranching (co)polymerization of glycidol with an epoxide monomer bearing disulfide groups, 2-((2-oxiran-2-ylmethoxy)ethyl)disulfanyl) ethan-1-ol. Polymerizations were optimized at 65 8C unlike the homopolymerization of glycidol. Both low (5-10 kDa) and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Glycidol is an established branching comonomer for anionic and cationic multibranching polyether synthesis. , Anionic polymerization using slow monomer addition (SMA) gives access to well-defined hyperbranched polyglycerols with a broad range of accessible molecular weights and rather narrow molecular weight distributions. , This technique has been successfully employed for the homopolymerization of glycidol and also for copolymerization with several glycidyl ethers. Via these comonomers, functional groups for “click” coupling reactions, biodegradable cleavage sites, and redox-responsive ferrocene moieties were introduced into the hyperbranched polyether structure in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…Glycidol is an established branching comonomer for anionic and cationic multibranching polyether synthesis. , Anionic polymerization using slow monomer addition (SMA) gives access to well-defined hyperbranched polyglycerols with a broad range of accessible molecular weights and rather narrow molecular weight distributions. , This technique has been successfully employed for the homopolymerization of glycidol and also for copolymerization with several glycidyl ethers. Via these comonomers, functional groups for “click” coupling reactions, biodegradable cleavage sites, and redox-responsive ferrocene moieties were introduced into the hyperbranched polyether structure in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…We sought the optimal conditions for a gram-scale batch size polymerization at 70 °C with a catalyst that renders reasonable yields, molecular weights above 10 kDa, low polydispersity (Đ), a sufficient degree of branching (DB) and incorporation of intact ester structures of the CL and disulfide bonds of the SSG, respectively. As has been stated by Kizhakkedathu et al before, typical temperatures for the ring-opening polymerization (ROP) of such monomers is around 95 °C; however, the SSG monomer is not stable and disulfide linkages undergo decomposition into thiols and thioethers [ 26 ]. Similar observations were made, and therefore, the polymerization temperature was kept strictly at 70 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Last, we showed that the individual amphiphilic polymers were able to function as nanocarriers to efficiently encapsulate hydrophobic organic dye molecules in aqueous solutions. We hope that the results from this study will not only provide new insights into the understanding of the relationship between molecular structure and thermoresponsive properties, but also enable the future design and production of intelligent polymer materials that can meet the requirements of specialized applications from hyperbranched copolymers. …”
Section: Discussionmentioning
confidence: 97%
“…We hope that the results from this study will not only provide new insights into the understanding of the relationship between molecular structure and thermoresponsive properties, but also enable the future design and production of intelligent polymer materials that can meet the requirements of specialized applications from hyperbranched copolymers. 83…”
Section: ■ Conclusionmentioning
confidence: 99%